Top Tips: How to design and manage adaptive programmes - Valters, Craig; Wild, Leni (Overseas Development Institute, 2019)
Within DFID, there is now a commitment to more flexible and adaptive p rogramming. This recognises that: • DFID works in contexts that contin uously evolve and change, sometimes in unpredictable ways. To respond to this, the agency needs to remain flexible – to expect change and ha ve a good understanding of context, with resources that can be adjuste d and scope to change direction if needed. All DFID programmes should be able to do this. • Some DFID programmes aim to support change in co mplex systems, behaviours and incentives. Efforts to address women’s e mpowerment, improve sanitation or build more sustainable health system s, for instance, all require engagement with the way in which complex systems operate and the people and behaviours within them. Trying to d eliver reforms in these circumstances is challenging because the pathw ay to reform itself will be unclear: as a reform is rolled out, the sy stem itself will react and respond. These types of programmes therefor e need to build in from the start deliberate processes of learning and testing, to allow for adaptations as more information is gathered for what works over time. These top tips are concerned with programmes th at aim to be flexible and adaptive – which work in dynamic contexts an d are trying to address complex problems. While there is growing commi tment to these approaches, feedback suggests staff still have question s about how to do this well. This document highlights some of the comm only reported issues related to adaptive programming and a set of tips , strategies and examples to help in addressing them. It is aimed at p rogramme managers and advisors who may be Senior Responsible Owners (S ROs) or those managing and supporting adaptive programming in a range of ways. We have collated these lessons from discussions with country offices and SROs, feedback from surveys and the wider evidence. We hav e looked specifically at the adaptive programmes we can find in the DF ID portfolio, but this is not an exhaustive list. It should be noted t hat there is as yet no wide variety of case law to review, but there i s a growing set of examples within DFID that can provide continuous le arning for the organisation.